How Thinking Routines Enhance Critical Thinking of Elementary Students - Mala Rejeki Manurung; Siti Masitoh; Fajar Arianto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Learning English as a foreign language within a primary school in Indonesia tends to be teacher-centered and focuses on the single correct answer. The demands of tests and covering textbook materials for tests prevent students from becoming active thinkers. Specific strategies have been proposed to promote critical thinking skills. Previous studies focused on applying thinking routines either in early childhood or higher education. This study examines the effect of thinking routines on sixth-grade elementary school students' critical thinking ability within an English lesson. The quasi-experimental research was conducted with 64 students divided into a control group (N=32) and an experimental group (N=32) at two different schools. This research was conducted online due to the COVID-19 pandemic. The data is analyzed statistically using the Mann-Whitney U Test. Critical thinking ability tests and observation sheets were used as data collection tools. The results reveal that thinking routines significantly improved sixth-grade students' critical thinking skills. The result suggests using thinking routines in teaching and learning to support students thinking from different points of view.